Sampling methods and censuses - Zarkovich, Slobodan S.; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 1965)
The main aim of this book was to promote the application of more recent achievements in the field of survey techniques, principally those involving sampling methods.
"First draft ... appeared in 1957 under title Sampling methods and censuses, volume I."
Includes bibliographical references and indexes.
aia 03/04/2018
Loans
Keywords: Sampling (Statistics); Census; Agriculture and statistics